A multi-sensor-based evaluation of the morphometric characteristics of Opa river basin in Southwest Nigeria. (2nd April 2020) - Adewole, Adedayo Oreoluwa; Ike, Felix; Eludoyin, Adebayo Oluwole
ABSTRACT: Studies have shown that many river basins in the sub-Saharan Africa are largely unmonitored, partly because they are poorly or totally ungauged. In this study, remote sensing products (Landsat, Advanced Spaceborne Thermal Emission and Reflection Radiometer; ASTER and Shuttle Radar Topography Mission; SRTM) that are freely available in the region were harnessed for the monitoring of Opa river basin in southwestern Nigeria. The remote sensing products were complementarily used with topographical sheets (1:50, 000), ground based observation and global positioning systems to determine selected morphometric characteristics as well as changes in landuse/landcover and its impact on peak runoff in the Opa river basin. Results showed that the basin is a 5 th order basin whose land area has been subjected to different natural and anthropogenic influences within the study period. Urbanisation is a major factor that threatens the basin with degradation and observed changes, and the threats are expected to become worse if restoration is not considered from some tributaries. The study concluded that commentary use of available remote sensing products in the region will provide an important level of decision support information for management and monitoring of river basins.